모바일게임 인앱결제 소비자피해 예방을 위한 연구 - 구혜경(Hye-Gyoung Koo); 김민지(Min-Ji Kim); 김수연(Su-Yeon Kim); 서도연(Do-Yeon Seo); 양소현(So-Hyeon Yang); 임정(Jeong Lim) (한국콘텐츠학회 논문지, 19(8), 2019)
This study want to identify problems related to mobile in-app payment from the perspective of consumers and suggest ways to solve them. Three scenarios have been developed to achieve the objectives of this study. This suggests the situation of in-app payment problem that consumers often experience. Then 323 consumers in their 20s and 30s read the scenario, identified the problem in each situation and assessed who was responsible. Consumers were aware of in-app payment problems due to problems with in-app payment readability, problems with app market responsibility, problems with responsibility of game companies, and problems of consumer responsibility. And different consumers had different levels of assessment on the problem of in-app payment. According to the research, consumers have high demand for improvement of the lack of readability in related laws, including strengthening the readability of the in-app payment indicator. In addition, the company confirmed the importance of cooperative efforts by consumers, businesses, and the government due to high consumer expectations for the role of the distribution company App Market other than the content developer game company. 모바일 콘텐츠 시장의 급성장과 더불어 인앱결제 관련 소비자 피해도 증가하고 있다. 본 연구에서는 소비자의 관점에서 모바일 게임 관련 인앱결제의 문제점을 파악하고 해결을 위한 방안을 제언하고자 인앱결제 관련 소비자문제 및 피해를 나타내는 3가지의 시나리오를 개발하였다. 그리고 2030 세대 323명이 각 상황을 통해 인앱결제 문제를 해결할 수 있는 방안을 평가하였다. 소비자들은 인앱결제 표시 및 가독성 문제, 앱마켓 책임 문제, 게임사 책임 문제, 소비자 책임 문제 등으로 인앱결제 문제를 인식하고 있었으며 각 요인에 대한 평가수준에 따라 표시개선 및 앱마켓 책임 강조형, 소비자 책임 강조형, 표시개선 및 게임사 책임 강조형으로 소비자가 유형화되었다. 유형별 특성을 파악하고 다항로짓분석을 통하여 인구통계적 특성 외에 인앱결제 표시 가독성 강화를 포함한 관련 법제의 미비점 개선에 대한 소비자의 요구가 높으며, 콘텐츠 개발사인 게임사 이외에 유통사인 앱마켓의 역할에 대한 소비자의 기대가 커 소비자, 기업, 정부의 협력적 노력이 중요함을 확인하였다.